“You are Dead, but You are Not”: Social medium (Facebook) is the message in grieving and continuing bonds - Huey Pyng Tan (Universitas Negeri Yogyakarta, 2020)
Today, one may no longer alive but his social networking sites (SNS) account will still live on. Empirical studies on death and SNS started since 2004 covering issues on grief, bereavement, mourning, relational continuity functions of SNS, and digital legacy. Majority of them applied content and discourse analyses on SNS messages directed to or related to the deceased. Applying McLuhan’s aphorism medium is the message, researcher focused on the interplay among forms and functions of Facebook (FB) as a medium and message that mediates grief and the bereaved persons who are communicators that decided to grieve on FB. This research adopts grounded theory approach where in- depth interviews with 10 bereaved persons who maintain relational continuity with their deceased loved ones through FB were conducted. The conclusions are drawn to prove that bereaved users preferred to engage in a transcoporeal mediated communication with deceased for continuing bonds due to four main reasons – the deceased are perceived “dead but they are not”; maintaining relational continuity via FB is essential to “finish their unfinished business”; they felt aided and embraced when adopting “FB the Public Platform for Private Grief”, and they imagined a mutual communication based on “past experience and religious belief”. The mediated transcopereal communication (TcC) is enabled because the social medium (FB) is the message.